Life cycle and cohort productivity in economic research: the case of Germany - Michael Rauber; Heinrich W. Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2007)
We examine the research productivity of German academic economists over their life cycles. It turns out that the career-patterns of research productivity as measured by journal publications are characterized by marked cohort effects. Moreover, the life-cycles of younger German economists are hump-shaped and closely resemble the life cycles identified for U.S. economists, whereas the life-cycles of older German economists are much flatter. Finally, we find that not only productivity, but also research quality follows distinct life cycles. Our study employs econometric techniques that are likely to produce estimates that are more trustworthy than previous estimates.
Keywords: A14; J24; 330; Wirtschaftswissenschaftler; Wirtschaftsforschung; Publikationsanalyse; Erwerbsverlauf; Deutschland